Uma abordagem de segurança do sistema Asterisk em plataformas embarcadas usando o protocolo SIP - Nogueira, Toniclay Andrade (2018)
The concern for security in Internet Protocol (IP) networks has been growing exponentially. Legal measures, such as severe penalties for cybercriminals, are already a reality. Several studies are being conducted to explore the security issues related to VoIP. On the other hand, embedded devices are increasingly efficient with complex and demanding systems. Free voice over IP software Asterisk aims to be a central telephone exchange, a viable alternative to be used in embedded devices being possible to reduce costs and maximize results. This master’s dissertation takes a security approach using Asterisk’s SIP protocol on embedded platforms. In parallel, it also aims to monitor the consumption of RAM, processing and power consumption in the moments of three Authentication, Man-in-the-middle and DoS Denial of Service security attacks. The results showed that the Raspberry Pi 3 device satisfactorily supports Authentication and Man-in-the-middle attacks, but the Asterisk system, in the Denial of Service attack, can not withstand the attack from five hundred thousand packets sent by the attacker, being unable to make calls having its operation totally neutralized. Regarding energy consumption, note that the Raspberry Pi 3 at its voltage tends to stay at an average level of 5.19v and Current ranging from -600.93mA to -832.41mA and Power ranging from -3132.40mV to -4314.78mV having parameterized the amount of packets sent by the attacker from 0 to 25,000,000.